Seroprevalence of Toxoplasma gondii in goats from the department of Piura, Peru - Fernández Rojas, Milagros (2023)
The aim of this study was to determine the seroprevalence of the Toxoplasma gondii parasite in goats from the department of Piura, Peru. In total, 362 serum samples were evaluated using a commercial indirect ELISA kit, which reveals the presence of IgG anti-T. gondii antibodies. The real seroprevalence was 26.29% (95% CI: 21.74 - 30.84%). The confidence intervals (95% CI) evidenced a significant difference (p<0.05) in the seropositive goats in relation to the altitudinal floor variable (0-500 vs 500-2500 m), while no significant difference was evidenced regarding the age group variable (<1, 1-3 and >3 years). The Odds Ratio (OR) between the sero-reactor animals and the altitudinal floor variable yielded a value of 0.37 (95% CI: 0.20 - 0.69), indicating that the altitude 0-500 m was a protective factor for toxoplasmosis infection in relation to 500-2500 m.